An Analisys Of The Main Character Moral Value In “Mulan 2020” Movie - Emilia Derodat Lero Kaka; I.B. Gde Nova Winarta (CV. Multi Kreasi Media, 2023)
This research deals with the main character moral value in “mulan 2020” movie. This research aims to analyze the main character moral value and types of the moral value conveyed by the main character. The research subject of this study was the main character in the Mulan 2020 movie as Mulan. The data was taken from the scenes and the scripts conveyed by the main character consisting of the moral value. The data were analyzed using the theory proposed by Linda and Eyre (1993). The data collecting procedure of this study was observation. The data were observed using note-taking techniques to identify and analyze the data. Data were analyzed using qualitative methods and presented descriptively. The result of this study showed that researchers found some moral values and types of moral values conveyed by the main character in the “Mulan 2020” movie.